Simultaneous detection method of muscle developing monoclonal antibodies with using LC-MS/MS from Dried Blood Spots - Hwang, Ji In; Lee, Hyeon-Jeong; SEO, YOON DAM; Eugene C. Yi; Hwa Jeong Lee; Min, Ho phil (American Society for Mass Spectrometry (ASMS), 2024)
Current treatments for muscle degeneration focus on diet, but TGF-β pathway manipulation (myostatin, activin A, GDF-11) shows promise. WADA bans these inhibitors for athletes. This study developed a detection method for target monoclonal antibodies (Landogrozumab, Domagrozumab, Bimagrumab, targeting TGF-β and Dulaglutide as a Internal standard. Using dried blood spots (DBS) and protein G magnetic beads for purification, followed by LC-MS/MS analysis. FAIMS was applicated to increase sensitivity of target unique peptides. Assays showed strong linearity (r = 0.99) and no interference issues. The matrix effect was near 100%, confirming DBS suitability for analysis. Though these antibodies lack clinical approval, this detection method is vital for doping control.